Mulheres distintas: o ensino de história e as representações de gênero a partir do Jornal da Manhã em Ponta Grossa (1954 - 1957) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
This research analyzed the representation of women in Jornal da Manhã, specifically in the years of circulation of the column “Da Mulher para a Mulher”, which also resulted in pedagogical proposals for the use of these historical sources in the teaching of History, in Basic Education. Among the objectives are to identify the representations of women in the column and to promote gender equity through debates that deconstruct the social representations of gender responsible for the production of stereotypes over time. The sources used were the column “Da Mulher para a Mulher” and articles that represented women in the Jornal da Manhã of Ponta Grossa. The time frame corresponded to the years 1954 to 1957, the period of circulation of the female column. The column presented different themes aimed at the construction and maintenance of the social roles established for women in the Pontifical elite. From this material, it was possible to develop a debate about the female representations printed in Jornal da Manhã, inside and outside the column. Through the thematic analysis of the subjects addressed, we sought to understand the press's commitment as a constructor and maintainer of distinct social roles and whose representations have perpetuated over time. The analysis methodology used was the theory of Social Representations, by means of the anchoring and objectification processes of Serge Moscovici (2012), with the Content Analysis tools of Laurence Bardin (2011) for the categorization of the column and its themes. The didacticization of the analyzes was proposed by the construction of didactic material to be used in the classroom, proposing an alternative that helps Education professionals in the construction of a democratic education, inclusive and free from gender bias.
Keywords: Ensino de História; Relações de Gênero; Papeis Sociais; Jornal; Jornal da Manhã; Representação social; History Teaching; Gender Relations; Social Roles; Newspaper; Jornal da Manhã; Social repreions; CNPQ::CIENCIAS HUMANAS::HISTORIA